Treatment Challenges in Multiple Sclerosis – A Continued Role for Glatiramer Acetate? - Mirabella, Massimiliano; Annovazzi, Pietro; Brownlee, Wallace; Cohen, Jeffrey A.; Kleinschnitz, Christoph; Wolf, Christian (Frontiers in Neurology, 2022)
Earlier diagnosis, access to disease-modifying therapies (DMTs), and improved supportive care have favorably altered the disease course of multiple sclerosis (MS), leading to an improvement in long-term outcomes for people with MS (PwMS). This success has changed the medical characteristics of the population seen in MS clinics. Comorbidities and the accompanying polypharmacy, immune senescence, and the growing number of approved DMTs make selecting the optimal agent for an individual patient more challenging. Glatiramer acetate (GA), a moderately effective DMT, interacts only minimally with comorbidities, other medications, or immune senescence. We describe here several populations in which GA may represent a useful treatment option to overcome challenges due to advanced age or comorbidities (e.g., hepatic or renal disease, cancer). Further, we weigh GA's potential merits in other settings where PwMS and their neurologists must base treatment decisions on factors other than selecting the most effective DMT, e.g., family planning, conception and pregnancy, or the need for vaccination.